The Response Growth and Production of Okra (Abelmoschus esculantus L. Moench) upon the Pruning Time of Shoots and NPK Fertilizing - Muhammad Sandy Prayudi; Asil Barus; Rosita Sipayung (Universitas Sumatera Utara, 2019)
Green okra characteristics are having straight stems and difficult to fork. High fruit production can be obtained in the presence of massive ramification. To form ramification and and fruit production, okra requires pruning of shoots with time and proper fertilization to support the growth of these branches and fruits. This reaserch was conducted at Desa Ladang Bambu, Kecamatan Medan Tuntungan, Medan (35m asl) from April to July 2017. The method used was factorial randomized block dsign with two treatment factors, i.e pruning of shoots (without pruning, age 15 and pruning of 30 days after planting) and NPK fertilization (2,5; 5,0; 7,5 and 10 gr per plant). The results of the study showed that the treatment purning time of shoots age of 15 days after planting significantly affect the parameter of branches quantity, number of productive branches, and weight of fruit per plant. While pruning of shoots age of 30 days after planting had significant effect on bar diameter and parameter of flowering age. NPK 7,5 gr fertilizer can significantly increase the number of productive branch and dose of 5,0 gr can improve the fruit circumference parameters. The interaction between the two treatments significantly affected the fruit circumference parameters.